An additional tool towards overcoming absence of specificity of carbon nanostructure-based electrochemical sensors-application to estriol and estradiol detection and distinction - Cesarino, Ivana [UNESP]; Huemmelgen, Ivo A. (Springer, 2015)
The tristimulus analysis was applied in differential pulse voltammetry experiments to detect and distinguish two substances using a set of three sensors that respond to both substances, aiming at the development of an additional tool to overcome the absence of specificity of the sensor to a single chemical species. The sensors are based on carbon nanostructures (graphene oxide, reduced graphene oxide, and reduced graphene oxide modified with antimony nanoparticles) and are applied to estriol and estradiol detection in water, which constitutes an environmental problem. We show that apart from substance identification, the method can be used to quantify the relative concentration of the substances in a solution.